A proposed in-service education program based on the competency needs of social studies teachers in Tacloban City - Tomayao, Erlinda M. (1978)
This paper aimed to propose an in-service education program in Social Studies based on the competency needs of Social Studies teachers in Tacloban City. The normative survey method was used. The main sources of data were answers to questionnaires given out to thirty-six secondary social studies teachers of Tacloban City. Afterwards, an in-service educatin program was evolved using the competency needs as basis. Review of related literature and studies were undertaken to determine what has been done along the proposed study and the gain suggestion and guidelines in carrying out the present research. It was concluded that the secondary social studies teachers in Tacloban City revealed competency needs in conducting the Inquiry Process in teaching social studies and how to prepare the Criterion Referenced Test.